Insects - Simon, Seymour (New York : Harper, 2016)
Explores the world of insects, including beetles, grasshoppers, ladybugs, bees, butterflies, dragonflies, and others, discussing their bodies, senses, life stages, and more.
Publisher's Weekly, June 2016
Booklist, May 2016
Includes index.
6.6
3-6
STEAM collection. Some copies purchased with funds from the Corvallis Public Schools Foundation.
Keywords: Insects -- Juvenile literature; Insects